Conjugated polymers constructed by a novel pyrene-fused polycyclic building block and their applications as organic electronic materials. (July 2016) - Wen, Hui; Gong, Xiaohui; Jia, Zhenhong; Han, Pei; Lin, Baoping; Ye, Shanghui; Sun, Ying; Zhang, Xueqin; Yang, Hong
Abstract: A large fused polycyclic pyrene derivative with five-membered imidazole rings fused onto pyrene core, 5, 11-Bis(5-Bromothiophene-2-yl)-4, 10-dioctadecyl-4, 10-dihydropyreno[4, 5-d:9, 10- d′]diimidazole (PBTI ), was designed as a new building block for the conjugated polymers. Copolymers of this monomer with vinylene (P1 ) and thiophene (P2 ) were synthesized and their physical properties and performance in organic thin film transistors were investigated. Both polymers exhibited highly coplanar backbones, similar lowest unoccupied molecular orbital energy levels at −3.7 ev and the uniform delocalized highest occupied molecular orbital with deep-lying energy levels around −5.7 ev. X-ray diffraction and grazing-incident X-ray diffraction measurements demonstrated that P2 adopted a highly ordered structure, thus giving an enhanced hole mobility of 0.015 cm 2  V −1  s −1 in organic thin film transistors. Graphical abstract: Highlights: Synthesis of a novel fused polycyclic building block for the conjugated polymers. Copolymers showed the good coplanarity and the uniform delocalized HOMO. Copolymer with an ordered structure exhibited a hole mobility of 0.015 cm 2  V −1  s −1 .